The association between polygyny statuses of currently married and in-union women and attitude towards intimate partner violence against women in Ghana. Issue 1 (2021) - Adewale, Dorcas; Dey, Nutifafa Eugene Yaw; Owusu Ansah, Kenneth; Duah, Henry Ofori; Agbadi, Pascal
Abstract: Polygyny is a common family structure in sub-Saharan African countries. Previous studies have documented that women in this family structure have favourable attitudes towards intimate partner violence (IPV). Nevertheless, there is limited recent research concerning this association in Ghana. This study sought to investigate the association between polygynous statuses and endorsement of IPV among Ghanaian reproductive-aged married and in-union women while controlling for covariates. The study used the nationally representative data from the 2017/2018 Ghana Multiple Indicator Cluster Survey. The sample comprised 7800 married/in-union women aged 15–49. Data analyses included tests of association and multivariable modelling using binary logistic regression. Compared to women in monogamous relations, their counterparts in polygynous relationships were more likely to support the justification for wife-beating if: wife goes out without telling husband (AOR = 1.44, 95% CI: 1.16, 1.80), neglects the children (AOR = 1.29, 95% CI: 1.07, 1.56) argues with husband (AOR = 1.56, 95% CI: 1.28, 1.90), refuses sex with husband (AOR = 1.54, 95% CI: 1.26, 1.90) and burns the food (AOR = 1.52, 95% CI: 1.14, 2.03). No significant relationship was found between women who have ever been in more than one union or marriage and justifications for IPV under any of the five circumstances. Some significant associations were found between other covariates and justifications for IPV under any of the five circumstances. The study revealed that women in polygynous relationships were more likely to support IPV. These findings extend the literature on the relationship between polygyny and endorsement of IPV among reproductive-age women in Ghana. It also contributes evidence towards strengthening interventions and policies geared towards changing attitudes of women in polygynous unions towards intimate partner violence.